Thermal Protection Strategies and Neuromonitoring during Ablation - Sag, Alan Alper; Husain, Aatif M. (Seminars in Interventional Radiology, 2022)
Advanced interventional pain management approaches seek to lesion neural targets to achieve desirable analgesia; however, equally important is preservation of motor and sensory function for regional bystander nerves. The topic of neuroprotection is also relevant for thermal ablation of metastatic bone tumors in the vicinity of neural structures. This report aims to provide an IR-directed framework of thermoprotective techniques available during thermal ablation.
Keywords: interventional radiology; cancer pain; pain management; analgesia; thermal ablation